1997
DOI: 10.1046/j.1365-2761.1997.d01-114.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of different challenge methods to evaluate the efficacy of furunculosis vaccines in Atlantic salmon, Salmo salar L.

Abstract: Four challenge methods, intraperitoneal (i.p.) and intramuscular (i.m.) inoculation, bath and cohabitation exposure, were evaluated as methods for testing the efficacy of furunculosis vaccines in Atlantic salmon, Salmo salar L. Groups of fish vaccinated with one of two different vaccines containing aluminium phosphate or animal/vegetable oil as an adjuvant were challenged with Aeromonas salmonicida 6 and 12 weeks after vaccination. Relative per cent survival (RPS) was calculated daily during a 3‐week observati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…However, the challenge data suggest strongly that the TTSS of A. salmonicida is required for host invasion. By immersion, a route of administration that requires host invasion to establish an overt disease state (Cardella & Eimers, 1990;Nordmo & Ramsted, 1997), an inactive secretory complex completely abolished virulence. The level of overt disease caused by DaopH was significantly reduced and DaexT was also attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…However, the challenge data suggest strongly that the TTSS of A. salmonicida is required for host invasion. By immersion, a route of administration that requires host invasion to establish an overt disease state (Cardella & Eimers, 1990;Nordmo & Ramsted, 1997), an inactive secretory complex completely abolished virulence. The level of overt disease caused by DaopH was significantly reduced and DaexT was also attenuated.…”
Section: Discussionmentioning
confidence: 99%
“…Nordmo [1,27] reviewed the strengths and weakness of different challenge methods used to determine the efficacy of fish vaccines. Immersion and cohabitation routes were considered the challenge methods that most closely mimic natural routes of infection [28].…”
Section: Discussionmentioning
confidence: 99%
“…Immersion and cohabitation routes were considered the challenge methods that most closely mimic natural routes of infection [28]. However, Nordmo [1,27] indicated that ip challenge was a reproducible and reliable means for the determination of vaccine efficacy. In addition, the ip route ensures that each individual fish receives a uniform challenge; however, it is generally considered to be the least natural route of infection, unless the fish are subject to skin puncture by infected fish [1,27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…V. salmonicida (VI 94/09/ 550) was grown in brain heart infusion broth (Difco, U.S.A.) containing 2% NaCl at 15 C, until the cell concentration reached 10 8 ml 1 , measured by a photometric method described by Nordmo & Ramstad (1997). The culture was inactivated with 0·5% v/v formalin (37%), and is henceforth referred to as V. salmonicida bacterin.…”
Section: Reagentsmentioning
confidence: 99%